2021
DOI: 10.7554/elife.64108
|View full text |Cite
|
Sign up to set email alerts
|

Multiple neuronal networks coordinate Hydra mechanosensory behavior

Abstract: Hydra vulgaris is an emerging model organism for neuroscience due to its small size, transparency, genetic tractability, and regenerative nervous system; however, fundamental properties of its sensorimotor behaviors remain unknown. Here, we use microfluidic devices combined with fluorescent calcium imaging and surgical resectioning to study how the diffuse nervous system coordinates Hydra's mechanosensory response. Mechanical stimuli cause animals to contract, and we find this response relies on at least two d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 78 publications
(122 reference statements)
1
21
0
Order By: Relevance
“…We confirmed that GCaMP7s successfully reported calcium activity by measuring fluorescence levels during contractions. As expected, based on prior calcium imaging [12,15,32], the neuronal activity in the peduncle showed increased calcium activity during contractions (Figure 1c,f, Supplemental Video S1). We also found that the tdTomato-positive neurons were a subpopulation of the neurons that were coactive during contractions, providing further evidence that ec5 neurons are part of the CB circuit (Figure 1b-g).…”
Section: Resultssupporting
confidence: 83%
“…We confirmed that GCaMP7s successfully reported calcium activity by measuring fluorescence levels during contractions. As expected, based on prior calcium imaging [12,15,32], the neuronal activity in the peduncle showed increased calcium activity during contractions (Figure 1c,f, Supplemental Video S1). We also found that the tdTomato-positive neurons were a subpopulation of the neurons that were coactive during contractions, providing further evidence that ec5 neurons are part of the CB circuit (Figure 1b-g).…”
Section: Resultssupporting
confidence: 83%
“…Previous studies have shown that cnidarians have several neural compartments with genetically distinct characteristics 12,13,34,46 . Specific neural activities associated with distinct behavioral responses have recently been reported: in the freshwater polyp Hydra 47,48 , which has a simple diffuse nervous system, and jellyfish 49 , which have developed distinct neural architectures, such as nerve rings. These findings lend further credence to the idea of functional compartmentalization in the pre-centralized nervous systems.…”
Section: Discussionmentioning
confidence: 99%
“…1C. Figure adapted from (Badhiwala et al, 2021) except that the ec1A spatial location has been adjusted to include the peduncle based on evidence provided by (Noro et al, 2019). Gene expression values are depicted by average expression across all cells (dot color) and percent expression within each cluster (dot size).…”
Section: Figure 1 the Hydra Vulgaris Nervous System Is Composed Of El...mentioning
confidence: 99%
“… ABSTRACT The small freshwater cnidarian polyp Hydra vulgaris uses adult stem cells (interstitial stem cells) to continually replace neurons throughout its life. This feature, combined with the ability to image the entire nervous system (Badhiwala et al, 2021; Dupre & Yuste, 2017) and availability of gene knockdown techniques (Juliano, Reich, et al, 2014; Lohmann et al, 1999; Vogg et al, 2022), makes Hydra a tractable model for studying nervous system development and regeneration at the whole-organism level. In this study, we use single-cell RNA sequencing and trajectory inference to provide a comprehensive molecular description of the adult nervous system.…”
mentioning
confidence: 99%